Business ethics an economically informed perspective - Lütge, Christoph 1969-; Uhl, Matthias 1980- (Oxford University Press, 2021)
In a globalized world, business ethics continues to gain importance as a field of study. Using a novel approach that centres on economic theory and analysis, this book provides students with a comprehensive overview of the essential concepts of business ethics related to both the economy as a whole and corporate ethics of the individual company
Keywords: Wirtschaftsethik; Lehrbuch